Comparison of hypertonic saline versus normal saline on cytokine profile during CABG - Mazandarani, Mahnaz (BioMed Central, 2012)
BACKGROUND AND THE PURPOSE OF THE STUDY: Blood contact with artificial surfaces of the extracorporeal circuit and ischemia-reperfusion injury in CABG with CPB, may lead to a systemic inflammatory response. Hypertonic saline have been recently investigated as a fluid in order to decrease inflammatory response and cytokines generation in patients undergo cardiac operations. Our purpose is to study the prophylactic effect of HS 5% infusion versus NS on serum IL-6 as an inflammatory & IL-10 as an anti-inflammatory biomarker in CABG patients. METHODS: The present study is a randomized double-blinded clinical trial. 40 patients undergoing CABG were randomized to receive HS 5% or NS before operation. Blood samples were obtained after receiving HS or NS, just before operation, 24 and 48 hours post-operatively. Plasma levels of IL-6 and IL-10 were measured by ELISA. RESULTS AND MAJOR CONCLUSION: Patients received HS had lower levels of IL-6 and higher level of IL-10 compared with NS group, however these differences were not statistically significant. Results of this study suggest that pre-treatment with small volume hypertonic saline 5% may have beneficial effects on inflammatory response following CABG operation.